Clinical Outcomes Associated with Home Mechanical Ventilation: A Systematic Review. (28th April 2016) - MacIntyre, Erika J.; Asadi, Leyla; Mckim, Doug A.; Bagshaw, Sean M.
Abstract : Background . The prevalence of patients supported with home mechanical ventilation (HMV) for chronic respiratory failure has increased. However, the clinical outcomes associated with HMV are largely unknown. Methods . We performed a systematic review of studies evaluating patients receiving HMV for indications other than obstructive lung disease, reporting at least one clinically relevant outcome including health-related quality of life (HRQL) measured by validated tools; hospitalization requirements; caregiver burden; and health service utilization. We searched MEDLINE, EMBASE, CINAHL, the Cochrane library, clinical trial registries, proceedings from selected scientific meetings, and bibliographies of retrieved citations. Results . We included 1 randomized control trial (RCT) and 25 observational studies of mixed methodological quality involving 4425 patients; neuromuscular disorders (NMD) (n = 1687 ); restrictive thoracic diseases (RTD) (n = 481 ); obesity hypoventilation syndrome (OHS) (n = 293 ); and others (n = 748 ). HRQL was generally described as good for HMV users. Mental rather than physical HRQL domains were rated higher, particularly where physical assessment was limited. Hospitalization rates and days in hospital appear to decrease with implementation of HMV. Caregiver burden associated with HMV was generally high; however, it is poorly described. Conclusion . HRQL and need for hospitalization may improve after establishment of HMV. These inferences are based on relatively few studies of marked heterogeneity and variable quality.